TOPICAL ASPECTS OF ASSESSING STRESS RESILIENCE IN PRESCHOOL EDUCATION SYSTEM TEACHERS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article presents theoretical information on the methodological foundations of diagnosing stress and stress resilience, which is among the key issues in modern psychology, particularly observed among educators in preschool educational institutions. The existence of stressful situations that significantly affect the physical and mental well-being of preschool teachers, and the ability to maintain a resilient attitude toward these stressors, is not only crucial for safeguarding their health but also plays a pivotal role in the effectiveness of their professional activities. Considering this, the issue of assessing and understanding stress resilience among preschool educators is gaining increasing scientific and practical importance. The article emphasizes the urgency of studying the psychological determinants of resilient responses to stress, especially in the context of early childhood education.